2017
DOI: 10.1007/978-3-319-55231-6_53
|View full text |Cite
|
Sign up to set email alerts
|

Potential Erythropoiesis in the Primo-Vascular System in Heart Failure

Abstract: The primo-vascular system (PVS), composed of primo-nodes (PNs) and primo-vessels (PVs), has been identified in various animal models. However, little is known about its function. Here, we investigated the changes in gross morphology and cellular composition of the organ-surface PVS (osPVS) in rats with heart failure (HF) induced by myocardial infarction. The size of the PNs in rats with HF was larger than in sham rats (1.87 vs. 0.80 mm; P < 0.01) and the density of osPVS per rat was greater for the HF rats (28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
2
10
0
3
Order By: Relevance
“…2) [18]. Moreover, the primo nodes and primo vessels in rats with heart failure showed significant erythropoiesis [31]. The major function of RBCs is to transport oxygen from the lungs to the tissues.…”
Section: Erythrocytesmentioning
confidence: 99%
“…2) [18]. Moreover, the primo nodes and primo vessels in rats with heart failure showed significant erythropoiesis [31]. The major function of RBCs is to transport oxygen from the lungs to the tissues.…”
Section: Erythrocytesmentioning
confidence: 99%
“…In case of bleeding and contamination of the PVS tissue by blood, such tissues were excluded from the analyses. Therefore, the red color in the some PVS tissues analyzed must be from the chromophore from the PVS tissue itself as shown previously [7]. For hematoxylin and eosin staining, the tissues were sectioned in paraffin and stained according to conventional protocols.…”
Section: ) Sampling Of the Ospvs Tissues And Stainingmentioning
confidence: 99%
“…The earlier observation on the erythropoietic changes in the primo nodes were further confirmed by recent studies using animal models of heart failure and acute hemolytic anemia. in 2017, Lim et al [7] showed in a rat model of heart failure (HF) that hyperplastic changes associated with hematopoiesis were observed in the primo vascular system (PVS) tissue isolated from the organ surface of the abdominal cavity (osPVS). In the study, there were significant increases in the number, size, and proportion of red-colored tissues in the osPVS in HF rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vascular circulatory system carries nutrients and oxygen to cells in living things, and the lymphatic circulatory system functions in eliminating pathogens and viruses. However, the PVS can be viewed as a circulatory system that plays a therapeutic function in regenerating the body tissues [8]. The current strategies for achieving cytokine inhibition include cytokine receptor inhibition and depletion of specific immune cells in addition to steroid therapy [9].…”
Section: Introductionmentioning
confidence: 99%